A wearable energy harvester unit using piezoelectric–electromagnetic hybrid technique - Hamid, Rawnak; Yuce, Mehmet Rasit (Sensors and actuators. A. Physical., 2017)
•This manuscript presents a new energy harvester that is suitable for wearable devices.•It combines electromagnetic and piezoelectric energy harvesters in one unit to harvest energy simultaneously from both transducers.•The design in this paper takes into account the attributes of both electromagnetic and piezoelectric energy harvesters to produce high output currents and high voltages for an efficient power generation method for wearable energy harvesting systems.•Detailed experimental results are presented. Wearable sensor electronics require a sustainable electrical power supply to operate. Energy harvesting techniques can be used to convert available nonelectrical energy sources into electrical energy. This paper presents WE-Harvest system, which is a new wearable energy harvesting system that combines piezoelectric and electromagnetic energy harvesters in one unit to generate a combined electrical energy source. Piezoelectric transducers are used to obtain sufficient regulated output voltages while electromagnetic is employed for its high power generation capability. Regular human body motions provide input vibrations for the proposed energy harvester unit. Several conditioning circuit topologies are proposed to efficiently extract energy from the two sources. The experimental results demonstrate that the combined topology enhances the power generation efficiency as well as enables stable output DC voltages. The dependence of energy harvester output on the load and input frequency has also been investigated.